Pengaruh Tanggung Jawab Sosial, Kerja Sama Dan Sistem Kerja Terhadap KinerjaKaryawan Rongsok Di Desa Karangtengah - Cindy Claudia Lindu Aji; Nunuk Supraptini; Sri Rahayu (Value : Jurnal Manajemen dan Akuntansi, 2026)
Scrap enterprises in the informal sector often face managerial challenges, including unclear work procedures, inconsistent task execution, weak worker coordination, and differing understandings of job responsibilities, which may reduce employee performance. This study examines the influence of Social Responsibility, Teamwork, and Work System on Employee Performance in scrap enterprises in Karangtengah Village. Using a quantitative associative approach, data were collected from 53 employees through Likert-scale questionnaires and analysed using SmartPLS. The findings indicate that Social Responsibility and Teamwork have not significantly improved employee performance. In contrast, the Work System plays a crucial role in enhancing performance, suggesting that employees work more effectively when supported by clear task allocation, structured procedures, and consistent operational regulations. These results demonstrate that, within informal sector businesses, employee performance is more strongly determined by organised work systems than by social or relational factors. This study contributes to human resource management literature by emphasising the importance of structured work systems in informal business environments. Practically, scrap business owners should prioritise systematic work arrangements, clear responsibilities, and standardised operating procedures to improve employee performance.